High-stability flow channel plate, preparation method thereof and liquid flow battery

CN122348214BActive Publication Date: 2026-09-08HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610823702.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-09-08
Estimated Expiration
2046-06-09

AI Technical Summary

Technical Problem

然而,等静压石墨导电性虽好耐腐蚀,但质地偏硬、多孔,不适合液流电池的压装和使用;石墨纸或石墨带导电性和耐腐蚀性虽好,但容易吸入电解液导致泡发、鼓泡和掉渣,堵塞流道造成电堆失效;柔性石墨导电性较好,但价格昂贵;导电碳塑虽然耐腐蚀、耐泡发,但是导电性一般,影响电堆高功率性能

Benefits of technology

[0016]第三方面,公开了一种液流电池,其特征在于,包括上述所述制备方法制备得到的高稳定性流道板或上述所述的高稳定性流道板;其中,

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122348214B_ABST
    Figure CN122348214B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of liquid flow batteries, and discloses a high-stability flow channel plate, a preparation method thereof and a liquid flow battery, which comprises the following steps: processing and shaping a conductive plate material, and performing plasma pretreatment to introduce active groups on the surface of the conductive plate material, so as to obtain a pre-oxidized flow channel plate; preparing film-forming slurry, wherein the film-forming slurry comprises a solvent, a dispersing agent, a perfluoroalkyl phosphonic acid and a conductive agent; soaking the pre-oxidized flow channel plate in the film-forming slurry, and performing a self-assembly reaction under light-proof conditions, so that the perfluoroalkyl phosphonic acid is chemically bonded with the active groups on the surface of the pre-oxidized flow channel plate through phosphonic acid groups, and the conductive agent is distributed in a hydrophobic film layer formed by the perfluoroalkyl phosphonic acid, so as to construct a hydrophobic conductive composite film; and cleaning and drying the flow channel plate after the reaction, so as to obtain the high-stability flow channel plate. The application has the advantages of high conductivity, hydrolysis resistance, acid and alkali resistance, high-temperature resistance, blistering resistance and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of flow battery technology, and in particular to a high-stability flow channel plate, its preparation method, and a flow battery. Background Technology

[0002] In recent years, flow batteries (such as vanadium redox flow batteries and iron-chromium flow batteries) have become one of the preferred technologies for large-scale, long-term energy storage applications due to their advantages such as independent design of power and capacity, high reliability, good safety, and long lifespan. The main challenge currently facing flow batteries is their high initial investment cost. To reduce the construction cost of flow battery systems, developing high-power-density stacks has become the preferred approach for most researchers. As the power density of the battery increases, its operating current density also increases, making the transport of active materials increasingly important in the entire electrode reaction process. Correspondingly, the proportion of concentration polarization in the polarization voltage gradually increases, and concentration polarization is mainly affected by the flow field structure. At this point, flow channels, such as the commonly used interdigitated flow channels and serpentine flow channels, are introduced to fully utilize the mass transfer advantages of flow batteries. Currently, the materials used to prepare the flow channel plates for flow batteries are mainly isostatic graphite, graphite paper (tape), flexible graphite, and conductive carbon plastic. Battery assembly is achieved by physically stacking a single flow channel plate with a bipolar plate or by integrating the flow channel plate and bipolar plate into a single integrated flow channel plate. However, while isostatic graphite has good conductivity and corrosion resistance, its hardness and porous nature make it unsuitable for the pressing and use of flow batteries. Graphite paper or graphite tape, while possessing good conductivity and corrosion resistance, easily absorbs electrolyte, leading to bubbling, foaming, and flaking, which can clog the flow channels and cause stack failure. Flexible graphite has good conductivity but is expensive. Conductive carbon plastic, although corrosion-resistant and resistant to bubbling, has only average conductivity, affecting the high-power performance of the stack. Therefore, the current technical challenge is to find a flow channel plate that is highly conductive, corrosion-resistant, resistant to bubbling, and low-cost to improve the performance and lifespan of flow batteries. Summary of the Invention

[0003] To address the aforementioned technical problems, this invention provides a highly stable flow channel plate, its preparation method, and a flow battery.

[0004] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, a method for preparing a highly stable flow channel plate is disclosed, comprising the following steps: Step S1: The conductive plate is processed and shaped, and then subjected to plasma pretreatment to introduce active groups on the surface of the conductive plate to obtain a pre-oxidized flow channel plate. Step S2: Prepare a film-forming slurry, the film-forming slurry comprising a solvent, a dispersant, a perfluoroalkylphosphonic acid, and a conductive agent; wherein the mass ratio of the perfluoroalkylphosphonic acid to the conductive agent is 0.1~0.5:1~5; Step S3: Immerse the pre-oxidized flow channel plate in the film-forming slurry and carry out a self-assembly reaction under light-protected conditions so that the perfluoroalkyl phosphonic acid chemically bonds with the active groups on the surface of the pre-oxidized flow channel plate through the phosphonic acid groups, and the conductive agent is interspersed in the hydrophobic film layer formed by the perfluoroalkyl phosphonic acid to construct a hydrophobic conductive composite film. Step S4: Clean and dry the reacted flow channel plate to obtain a high-stability flow channel plate.

[0005] In one implementation, in step S1: The plasma pretreatment uses a mixture of oxygen and argon, wherein the volume percentage of oxygen is 20% to 40% and the volume percentage of argon is 60% to 80%.

[0006] In one implementation, in step S1: The process parameters for plasma pretreatment are: processing power 60~300W, gas pressure 100~500Pa, gas flow rate 0.2~5L / min, and processing time 30~60s.

[0007] Under low or normal pressure, plasma generated by an oxygen / argon mixture is used to bombard the surface of the flow channel plate, introducing active oxygen species (such as O•, OH•) to react with carbon atoms in situ to generate active groups of hydroxyl and carbonyl groups. At the same time, the etching effect of argon plasma forms a large number of micropits on the surface of the flow channel plate, which helps to enhance the adhesion between the substrate and the subsequent coating. This pretreatment method does not damage the bulk structure and has no solvent pollution, and can precisely control the functional group density and surface morphology.

[0008] In one implementation, in step S2: The perfluoroalkylphosphonic acid is selected from one of perfluorobutylphosphonic acid, perfluorohexylphosphonic acid, perfluorooctylphosphonic acid, perfluorodecylphosphonic acid, and perfluorododecylphosphonic acid; The dispersant is selected from polyacrylic acid and polyvinylpyrrolidone; The solvent is selected from one of methanol, ethanol, acetone, dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, and N,N-dimethylacetamide; The conductive agent is selected from one of single-walled carbon nanotubes, multi-walled carbon nanotubes, activated carbon, and graphene.

[0009] The core components of the film-forming slurry are perfluoroalkyl phosphonic acid and a conductive agent. The structure of perfluoroalkyl phosphonic acid consists of a strongly anchored phosphonic acid end and a perfluoroalkyl low surface energy chain. On the one hand, the phosphonic acid group of perfluoroalkyl phosphonic acid can undergo dehydration condensation with active groups such as hydroxyl groups on the surface of the flow channel plate to form stable POC covalent bonds or bidentate coordination bonds. The bonding strength is much higher than that of silane coupling agents and ordinary alkyl thiols. It has the advantages of hydrolysis resistance, acid and alkali resistance, high temperature resistance, and long-term physiological environment immersion resistance. It is not easy to fall off and provides extreme stability for the interface. On the other hand, the perfluoroalkyl chain at the core functional end of perfluoroalkyl phosphonic acid has extremely high CF bond energy, which endows the molecule with extremely low surface energy, strong hydrophobicity and oleophobicity, and excellent chemical inertness. It can form a superhydrophobic interface on the substrate surface that is not wetted by water or oil. At the same time, it is resistant to oxidation, solvents, and biocorrosion, which significantly improves the substrate's antifouling, anticorrosion, and anti-aging properties. The function of the conductive agent is to enable the hydrophobic film layer formed by perfluoroalkyl phosphonic acid to have high conductivity. The hydrophobic conductive composite film formed by the combination of perfluoroalkyl phosphonic acid and conductive agent perfectly combines the strong covalent anchoring ability of phosphonic acid groups with the extremely low surface energy and high chemical stability of perfluorocarbon chains and the high conductivity of conductive agent.

[0010] In one implementation, in step S2: The solvent has a mass fraction of 93.5-98.7%, the dispersant has a mass fraction of 0.2-1%, the perfluoroalkylphosphonic acid has a mass fraction of 0.1-0.5%, and the conductive agent has a mass fraction of 1-5%.

[0011] In one implementation, in step S3: The process conditions for the self-assembly reaction are: reaction temperature 40~60℃, soaking time 1~3h.

[0012] The self-assembly film formation reaction is carried out under light-protected conditions because perfluoroalkylphosphonic acids are hygroscopic and photosensitive. Subsequent drying steps with ethanol, pure water, and nitrogen can prevent unbound molecules from remaining on the flow channel plate surface and affecting performance.

[0013] In one implementation, in step S1: The conductive material is selected from one of natural graphite plate, isostatic graphite plate, and graphite paper. The conductive plate after processing is shaped as a finger-type flow channel plate or a serpentine flow channel plate.

[0014] Secondly, a high-stability flow channel plate is disclosed, which is prepared by the high-stability flow channel plate preparation method described above.

[0015] In one embodiment, the substrate surface of the high-stability flow channel plate is bonded with a hydrophobic and conductive composite film via POC covalent bonds, the hydrophobic and conductive composite film comprising perfluoroalkyl segments and a conductive network; The resistivity of the high-stability flow channel plate is no higher than 2.28 mΩ•cm.

[0016] Thirdly, a flow battery is disclosed, characterized in that it comprises a high-stability flow channel plate prepared by the above-described preparation method or the high-stability flow channel plate described above; wherein... The weight gain of the high-stability flow channel plate after immersion in the electrolyte of the flow battery for 5 days is no more than 0.3%.

[0017] The beneficial effects of the present invention include at least the following: 1. This invention generates a hydrophobic and conductive composite film on the surface of a conductive plate with graphite as the substrate through self-assembly. This composite film not only has super hydrophobicity, but its core component, perfluoroalkylphosphonic acid, has a unique molecular structure and excellent interfacial properties. When it reacts with a pre-oxidized flow channel plate, it forms stable POC covalent bonds or bidentate coordination bonds, with a bonding strength far exceeding that of silane coupling agents and common alkyl thiols. It has the advantages of being resistant to hydrolysis, acids and alkalis, high temperatures, and long-term immersion in physiological environments. Moreover, it also has high conductivity. Due to the addition of a conductive agent to the film-forming slurry, the conductivity of the film is improved without affecting the bulk resistance and contact resistance of the flow battery, and has no impact on battery performance.

[0018] 2. The high-stability flow channel plate prepared by this invention can be applied to various flow batteries. The hydrophobic and conductive composite film on the surface of the flow channel plate makes it difficult for the electrolyte to enter the interior of the conductive plate and cause foaming problems. It also provides extreme stability to the interface, resists long-term scouring by electrolyte without falling off, and provides good conductivity to the battery.

[0019] 3. The preparation method of the high-stability flow channel plate of the present invention is simple and can be mass-produced. Compared with the integrated flow channel plate, the conductive plate in the present invention can use low-cost graphite substrate (such as graphite paper), which can significantly reduce the cost of battery. Attached Figure Description

[0020] Figure 1 This is a flowchart illustrating the preparation process of the high-stability flow channel plate of the present invention.

[0021] Figure 2 This is a cross-sectional view of the flow channel plate surface after a hydrophobic conductive film has been formed in Example 1.

[0022] Figure 3 This is a cross-sectional view of the flow channel plate in Comparative Example 1.

[0023] Figure 4 This is a contact angle test diagram of the flow channel plate in Example 1.

[0024] Figure 5 This is a test diagram of the contact angle of the flow channel plate in Comparative Example 1. Detailed Implementation

[0025] The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0026] like Figure 1 As shown, conductive substrates (such as natural graphite plates, isostatic graphite plates, graphite paper, and flexible graphite plates) are processed into flow channel plates (such as interdigitated flow channel plates and serpentine flow channel plates) of the required shape for flow batteries. The flow channel plates are then subjected to plasma pretreatment. The plasma gas is a mixture of oxygen and argon, with a volume ratio of oxygen: 20%~40% and argon: 60%~80%, respectively. The mixed gas flow rate is 0.2~5 L / min, the gas pressure is 100~500 Pa, the plasma pretreatment power is 60~300 W, and the treatment time is 30~60 minutes. After s, a pre-oxidized flow channel plate is obtained; 0.1~0.5 parts by mass of perfluoroalkylphosphonic acid and 0.2~1 parts by mass of dispersant are dissolved in 93.5~98.7 parts by mass of solvent, and 1~5 parts by mass of conductive agent are added. The mixture is prepared into a film slurry by sand milling. The pre-oxidized flow channel plate is immersed in the film-forming slurry in the dark for 1~3 hours. The self-assembly film-forming reaction temperature is 40~60℃ to complete the self-assembly film-forming reaction. A hydrophobic and conductive composite film is formed on the surface of the pre-oxidized flow channel plate. After rinsing with ethanol and deionized water and drying with nitrogen, a high-stability flow channel plate is obtained.

[0027] The present invention will be described in detail below through examples.

[0028] Example 1: The following technical solution is adopted. Natural graphite plates were processed into finger-shaped flow channel plates required for flow batteries. The flow channel plates underwent plasma pretreatment using an oxygen / argon mixture with a ratio of 20% oxygen and 80% argon. The flow rate was 0.2 L / min, the pressure was 100 Pa, the pretreatment power was 60 W, and the treatment time was 30 s, resulting in a pre-oxidized flow channel plate. 0.1 parts by weight of perfluorobutylphosphonic acid and 0.2 parts by weight of polyvinylpyrrolidone were dissolved in 98.7 parts by weight of methanol, and 1 part by weight of single-walled carbon nanotubes were added. A film slurry was prepared using a sand mill. The pre-oxidized flow channel plate was then immersed in the film-forming slurry in the dark for 1 hour. The self-assembly film formation reaction temperature was 40℃. After the self-assembly film formation reaction was completed, a hydrophobic and conductive composite film was formed on the surface of the pre-oxidized flow channel plate. After rinsing with ethanol and deionized water and drying with nitrogen, a highly stable flow channel plate was obtained, as shown in the cross-sectional diagram below. Figure 2 As shown. Figure 4This is a contact angle test diagram of the flow channel plate in this embodiment, with a contact angle of 149.5°, for comparison. Figure 5 The image shows the contact angle test result of the flow channel plate in Comparative Example 1. The contact angle is 22.1°, mainly because there is a hydrophobic conductive composite film on the surface of the flow channel plate prepared in this embodiment.

[0029] Example 2: The following technical solution is adopted. Isostatically pressed graphite plates were processed into serpentine flow channel plates of the required shape for flow batteries. The flow channel plates were then subjected to plasma pretreatment using an oxygen / argon mixture with a ratio of 25% oxygen and 75% argon. The flow rate of the mixture was 1 L / min, the pressure was 150 Pa, the plasma pretreatment power was 100 W, and the treatment time was 35 s to obtain a pre-oxidized flow channel plate. 0.2 parts by weight of perfluorooctylphosphonic acid and 0.4 parts by weight of polyacrylic acid were dissolved in 97.4 parts by weight of dimethyl sulfoxide, and 2 parts by weight of activated carbon were added. The mixture was then prepared into a film slurry using a sand mill. The pre-oxidized flow channel plate was immersed in the film-forming slurry in the dark for 1.5 h. The self-assembly film-forming reaction temperature was 45 °C to complete the self-assembly film-forming reaction, forming a hydrophobic and conductive composite film on the surface of the pre-oxidized flow channel plate. After rinsing with ethanol and deionized water and drying with nitrogen, a high-stability flow channel plate was obtained.

[0030] Example 3: The following technical solution is adopted. Natural graphite plates were processed into interdigitated flow channel plates of the required shape for flow batteries. The flow channel plates were then subjected to plasma pretreatment using an oxygen / argon mixture with a ratio of 30% oxygen and 70% argon. The flow rate of the mixture was 3 L / min, the pressure was 200 Pa, the plasma pretreatment power was 200 W, and the treatment time was 40 s to obtain a pre-oxidized flow channel plate. 0.3 parts by weight of perfluorohexylphosphonic acid and 0.6 parts by weight of polyvinylpyrrolidone were dissolved in 96.1 parts by weight of ethanol, and 3 parts by weight of multi-walled carbon nanotubes were added. The mixture was then prepared into a film slurry using a sand mill. The pre-oxidized flow channel plate was immersed in the film-forming slurry in the dark for 2 hours. The self-assembly film-forming reaction temperature was 50°C to complete the self-assembly film-forming reaction, forming a hydrophobic and conductive composite film on the surface of the pre-oxidized flow channel plate. After rinsing with ethanol and deionized water and drying with nitrogen, a high-stability flow channel plate was obtained.

[0031] Example 4: The following technical solution is adopted. Graphite paper was processed into a serpentine flow channel plate of the required shape for a flow battery. The flow channel plate was then subjected to plasma pretreatment using an oxygen / argon mixture with a ratio of 35% oxygen and 65% argon. The flow rate of the mixture was 4 L / min, the pressure was 300 Pa, the plasma pretreatment power was 250 W, and the treatment time was 50 s to obtain a pre-oxidized flow channel plate. 0.4 parts by weight of perfluorodecylphosphonic acid and 0.8 parts by weight of polyacrylic acid were dissolved in 94.8 parts by weight of N,N-dimethylformamide, and 4 parts by weight of activated carbon were added. The mixture was then prepared into a film slurry using a sand mill. The pre-oxidized flow channel plate was immersed in the film-forming slurry in the dark for 2.5 h. The self-assembly film-forming reaction temperature was 55 °C to complete the self-assembly film-forming reaction, forming a hydrophobic and conductive composite film on the surface of the pre-oxidized flow channel plate. After rinsing with ethanol and deionized water and drying with nitrogen, a high-stability flow channel plate was obtained.

[0032] Example 5: The following technical solution is adopted. Natural graphite plates were processed into interdigitated flow channel plates of the required shape for flow batteries. The flow channel plates were then subjected to plasma pretreatment using an oxygen / argon mixture with a ratio of 40% oxygen and 60% argon. The flow rate of the mixture was 5 L / min, the pressure was 500 Pa, the plasma pretreatment power was 300 W, and the treatment time was 60 s to obtain a pre-oxidized flow channel plate. 0.5 parts by weight of perfluorododecylphosphonic acid and 0.1 parts by weight of polyvinylpyrrolidone were dissolved in 93.5 parts by weight of N,N-dimethylacetamide, and 5 parts by weight of graphene were added. The mixture was prepared into a film slurry using a sand mill. The pre-oxidized flow channel plate was then immersed in the film-forming slurry in the dark for 3 hours. The self-assembly film-forming reaction temperature was 60°C to complete the self-assembly film-forming reaction, forming a hydrophobic and conductive composite film on the surface of the pre-oxidized flow channel plate. After rinsing with ethanol and deionized water and drying with nitrogen, a high-stability flow channel plate was obtained.

[0033] Comparative Example 1: The following technical solution is adopted. Step S1 is the same as in Example 3, except that the subsequent steps S2, S3, and S4 are not performed. Its cross-sectional view is shown below. Figure 3 As shown.

[0034] Comparative Example 2: The following technical solution is adopted. Steps S1-S2 are the same as in Example 3, except that the subsequent film-forming treatments S3 and S4 are not performed.

[0035] The flow channel plates prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to resistivity and electrolyte adsorption weight gain tests under the same test conditions. The test results are shown in Table 1. Table 1. Test results of flow channel plate resistivity and electrolyte adsorption weight gain.

[0036] As shown in Table 1, Comparative Example 1 is equivalent to no conductive treatment, with a resistivity of 2.25 mΩ⋅cm and a weight gain of 20% after 5 days of electrolyte immersion. Comparative Example 2, after plasma treatment, has resistivity and weight gain almost identical to Comparative Example 1, indicating that the hydrophobicity and conductivity of the flow channel plate remained unchanged before and after plasma treatment. The flow channel plates in Examples 1-5, after plasma treatment and self-assembly film formation, exhibit resistivity values ​​very close to Comparative Example 1, indicating that the hydrophobic conductive film formed on the surface of the flow channel plate hardly reduced its bulk conductivity, and its impact on battery performance is predictably negligible. Unlike the comparative examples, Examples 1-5 show a significant improvement in weight gain after 5 days of electrolyte immersion, indicating that the hydrophobic conductive composite film formed on the surface of the flow channel plate has excellent hydrophobicity, greatly preventing electrolyte from entering the flow channel plate and avoiding bubbling and swelling problems. This is because a hydrophobic conductive film is self-assembled on the surface of the graphite-based conductive plate. This film not only has super hydrophobicity, but its core component, perfluoroalkylphosphonic acid, has a unique molecular structure and excellent interfacial properties. When it reacts with the pre-oxidized flow channel plate, it forms stable POC covalent bonds or bidentate coordination bonds. The bonding strength is much higher than that of silane coupling agents and common alkyl thiols. It has the advantages of being resistant to hydrolysis, acid and alkali, high temperature, and long-term physiological immersion, providing extreme stability to the interface and greatly extending the service life of the flow channel plate.

[0037] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a high-stability flow channel plate, characterized in that, Includes the following steps: Step S1: The conductive plate is processed and shaped, and then subjected to plasma pretreatment to introduce active groups on the surface of the conductive plate to obtain a pre-oxidized flow channel plate; the process parameters of the plasma pretreatment are: processing power 60~300W, gas pressure 100~500Pa, gas flow rate 0.2~5L / min, and processing time 30~60s; the conductive plate is selected from one of natural graphite plate, isostatic graphite plate, and graphite paper; Step S2: Prepare a film-forming slurry, which includes a solvent, a dispersant, a perfluoroalkylphosphonic acid, and a conductive agent; wherein the mass ratio of the perfluoroalkylphosphonic acid to the conductive agent is 0.1~0.5:1~5; the perfluoroalkylphosphonic acid is selected from one of perfluorobutylphosphonic acid, perfluorohexylphosphonic acid, perfluorooctylphosphonic acid, perfluorodecylphosphonic acid, and perfluorododecylphosphonic acid; the conductive agent is selected from one of single-walled carbon nanotubes, multi-walled carbon nanotubes, activated carbon, and graphene; Step S3: Immerse the pre-oxidized flow channel plate in the film-forming slurry and carry out a self-assembly reaction under light-protected conditions so that the perfluoroalkyl phosphonic acid chemically bonds with the active groups on the surface of the pre-oxidized flow channel plate through the phosphonic acid groups, and the conductive agent is interspersed in the hydrophobic film layer formed by the perfluoroalkyl phosphonic acid to construct a hydrophobic conductive composite film. Step S4: Clean and dry the reacted flow channel plate to obtain a high-stability flow channel plate.

2. The preparation method according to claim 1, characterized in that, In step S1: The plasma pretreatment uses a mixture of oxygen and argon, wherein the volume percentage of oxygen is 20% to 40% and the volume percentage of argon is 60% to 80%.

3. The preparation method according to claim 1, characterized in that, In step S2: The dispersant is selected from polyacrylic acid and polyvinylpyrrolidone; The solvent is selected from one of methanol, ethanol, acetone, dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, and N,N-dimethylacetamide.

4. The preparation method according to claim 1, characterized in that, In step S2: The solvent has a mass fraction of 93.5-98.7%, the dispersant has a mass fraction of 0.2-1%, the perfluoroalkylphosphonic acid has a mass fraction of 0.1-0.5%, and the conductive agent has a mass fraction of 1-5%.

5. The preparation method according to claim 1, characterized in that, In step S3: The process conditions for the self-assembly reaction are: reaction temperature 40~60℃, soaking time 1~3h.

6. The preparation method according to claim 1, characterized in that, In step S1: The conductive plate after processing is shaped as a finger-type flow channel plate or a serpentine flow channel plate.

7. A high-stability flow channel plate, characterized in that, It is prepared using the high-stability flow channel plate preparation method as described in any one of claims 1 to 6.

8. The high-stability flow channel plate according to claim 7, characterized in that, The surface of the high-stability flow channel plate is bonded with a hydrophobic and conductive composite film via POC covalent bonds. The hydrophobic and conductive composite film contains perfluoroalkyl segments and a conductive network. The resistivity of the high-stability flow channel plate is no higher than 2.28 mΩ·cm.

9. A flow battery, characterized in that, This includes the high-stability flow channel plate prepared by the preparation method according to any one of claims 1 to 6, or the high-stability flow channel plate according to any one of claims 7 to 8; wherein, The weight gain of the high-stability flow channel plate after immersion in the electrolyte of the flow battery for 5 days is no more than 0.3%.

Citation Information

Patent Citations

  • Composition for increasing the lipophobicity of a watch-making component

    CN103476908A

  • Bipolar plate for all-vanadium redox flow battery as well as surface modification method and application of bipolar plate

    CN121839741A